Increasing water vapor transport to the Greenland Ice Sheet revealed using self‐organizing maps. Issue 17 (14th September 2016) - Mattingly, Kyle S.; Ramseyer, Craig A.; Rosen, Joshua J.; Mote, Thomas L.; Muthyala, Rohi
Abstract: The Greenland Ice Sheet (GrIS) has been losing mass in recent decades, with an acceleration in mass loss since 2000. In this study, we apply a self‐organizing map classification to integrated vapor transport data from the ERA‐Interim reanalysis to determine if these GrIS mass loss trends are linked to increases in moisture transport to Greenland. We find that "moist" days (i.e., days featuring anomalously intense water vapor transport to Greenland) were significantly more common during 2000–2015 compared to 1979–1994. Furthermore, the two most intense GrIS melt seasons during the last 36 years were either preceded by a record percentage of moist winter days (2010) or occurred during a summer with a record frequency of moist days (2012). We hypothesize that moisture transport events alter the GrIS energy budget by increasing downwelling longwave radiation and turbulent fluxes of sensible and latent energy. Key Points: Patterns of anomalously strong water vapor transport to Greenland‐identified using self‐organizing maps‐are increasing in frequency Increasing water vapor transport to Greenland coincides with accelerating melt of the Greenland Ice Sheet (GrIS) Moisture transport events likely enhance downwelling longwave radiation and turbulent fluxes of sensible and latent heat